Genetics of Charcot-Marie-Tooth Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The nomenclature, classification, and genetic basis of Charcot-Marie-Tooth (CMT) disease are reviewed from the Department of Molecular and Cell Biology, University of Aberdeen Medical School, Scotland.